PROMOTION MIX, INDIVIDUAL INTERNAL ENVIRONMENT, AND PURCHASE DECISION MAKING IN MINIMARKET - Apri Budianto; Irma Darmawati Bastaman; Ferey Herman (Jurnal Bisnis Manajemen, 2020)
This study analyzes the effect of the promotion mix and the internal environment of individuals on consumer purchasing decisions. The promotion mix has a positive relationship with purchasing decisions because consumers will be introduced to various products and influence the desire of consumers to buy these products. Meanwhile the positive relationship of an individual’s internal environment with consumer purchasing decisions will, therefore, be a consideration in making decisions. The new contribution of this study concerns the relationship between the promotion mix literature and the separate internal environment of individuals regarding consumer purchasing decisions. To test the hypothesis, we use the parametric statistical analysis method through Structural Equation Modeling. We conducted this study on the perceptions of minimarket consumers in the Priangan Timur region in Indonesia, whereas many as 400 customers were selected randomly. The results of the study show that the promotion mix and the internal environment of individuals influence consumer purchasing decisions. Other results show that the promotional mix applied by minimarkets based on consumer perceptions gets an attractive category. While the individual’s internal environment based on consumer perception becomes a consideration in making a decision.